Assessing the utility of open-source data in exploring benthic biodiversity in mining concessions off the South African coast - Lennox, Emma (Department of Biological Sciences, 2023)
Extractive activity in the marine realm is a well-recognised pressure on the marine environment, particularly for the preservation of biodiversity (Majiedt et al. 2019). Data that are openly available, from repositories, guides and within other studies, are a growing resource available to researchers, with the benefits including accessibility, cost effectiveness, and access to long-term data. Data were sourced from the Ocean Biodiversity Information System (OBIS), Offshore Invertebrate Field Guide (Atkinson and Sink) and mining impact datasets (Steffani and Pulfrich 2008, Cook 1995, 1996, 1997 and 1999) to explore the utility of openly available data in exploring benthic biodiversity within two mining concessions on the west and south coasts of South Africa. Lists of benthic taxa were generated, and biodiversity quantified using quantitative measures (species richness, Shannon-Wiener index) and multivariate analyses, where possible. Each dataset provided a different aspect of the benthic biota within the concessions, including taxonomic data (i.e., species, genera, class, phylum) that are easily quantified within a particular region. Long-term data available from OBIS allowed for patterns to be visualised over time, although this was constrained by data gaps, differences in methodology and lack of metadata, for instance. For the purposes of assessing how anthropogenic pressure impacts biodiversity, the utility of open-source data was limited to datasets that considered the impacts of mining in particular. To consider the impacts different types of extractive activity have on biodiversity at a finer scale, in-situ sampling of the proposed area is substantially more beneficial than open-source data in assessing the particular ways ecosystems are impacted by anthropogenic activity.